Investigating the protective effect of glutamine against cerebral ischemia and bilateral carotid occlusion in rats. - Bakhshaliyev, Shiraslan; Arslanoğlu, Ergin; Çitoğlu, Görkem; Akif Önalan, Mehmet; Altunyuva, Kaan; Canbay Sarılar, Çağla; Küçükgergin, Canan; Doğru-Abbasoğlu, Semra; Kıran, Tuğçe; Bozbuğa, Nilgün (My University, 2022)
This study aims to investigate the protective effects of glutamine against cerebral injury resulting from cerebral ischemia-reperfusion by bilateral carotid occlusion in rats.

Eighteen Wistar albino rats were randomly divided into three equal groups: 1) control group; 2) ischemia-reperfusion group which underwent clamping of the carotid artery for 20 min; and 3) ischemiareperfusion + glutamine group which was treated with two doses of glutamine (1 g/kg) prior to the same clamping procedure as the ischemia-reperfusion group. All rats were sacrificed 24 h after the experiment. Their brain tissue was removed, separated into right and left hemispheres, and sent for analysis. Biochemical analysis was used to determine the oxidant parameters, antioxidant parameters, and glutathione levels in brain tissue. In the histopathological analysis of the brain tissue, ischemic markers such as red neurons, spongiosis, and satellitosis were examined.

Biochemical examination revealed that the levels of malondialdehyde and ferric reducing antioxidant power in the ischemia-reperfusion group were significantly higher than those in the control and ischemia-reperfusion + glutamine groups (p<0.05). The histopathological findings revealed that the levels of red neurons, satellitosis, and spongiosis in the ischemia-reperfusion group were significantly higher than those in the control group (p<0.05). The red neuron and spongiosis levels in the ischemia-reperfusion + glutamine group were significantly higher than those in the control group (p<0.05).

Our study findings indicate that glutamine treatment has a protective effect against ischemia-reperfusion-induced brain damage in rats.
Keywords: Glutamine; ischemia-reperfusion injury; rats